Ownership Patterns of Land Rights from the Perspective of Customary Law Communities in Waropen Regency Papua Province - Daniel Tanati (Dinasti Research, 2024)
Ownership of land rights in the Waropen customary law community is very important because the land is a legacy of their ancestors which is used to meet their daily needs. The aim of this research is to find out more about land ownership rights from the perspective of the Waropen customary law community. The approach used is empirical, which looks directly at the reality that occurs among the Waropen traditional law community regarding ownership of land rights which are considered a legacy from their ancestors and are used to meet their daily needs. Data obtained from field observations, both primary and secondary, are then analyzed systematically so that the data can be accounted for. The results of this research reveal that the Waropen Indigenous people recognize 2 (two) types of land rights, namely ownership rights and use rights. Residents of the Waropen indigenous community can have property rights in the form of individual rights, family property rights which are the same as household property rights, and clan property rights or customary rights. Property rights in the Waropen language are called Mipena (Sanggei Village) or Risanau. Mipena or risanau in the traditional concept is originally a former garden. Former garden land refers to ownership of land or an area that is owned. Meanwhile, the right to use is the right to use or collect proceeds from land controlled by the state or land owned by another person, based on a mutual agreement between the land owner and the person who will use the land. In the Waropen indigenous community, this right of use can be differentiated into several groups of users of land rights, including the right to use for fellow Waropen people, this transfer is facilitated by the Government, the right to use for pastors, evangelists, teachers, health workers who come to dedicate themselves in the Waropen area and use rights are also given to traders from Bugis, Makassar, Java and Toraja as a place to carry out business activities.